Gender Representation in Politics And its Impact on Policymaking - Aquino, Rafael; Eduardo, Ramon; Ana, Maria (Journal Social Humanity Perspective, 2023)
This study used a qualitative research design to investigate the barriers to political engagement faced by women and gender minorities, as well as how gender diversity in politics affects policy results. This study dives into the experiences, viewpoints, and hurdles that impede gender representation in politics through in-depth interviews with political officials, policymakers, and gender advocates, as well as focus group talks with citizens and activists. Thematic analysis indicates the persistence of gender stereotypes, institutional and systemic barriers, political violence, and cultural norms that restrict women's and gender minorities' full and equal involvement. this study reveals the importance of gender representation in policymaking. Gender-diverse legislatures highlight social welfare issues and fight for gender equality and social justice measures. When women and gender minorities participate actively in political decision-making, policies become more inclusive, addressing the specific interests and concerns of varied communities. This study emphasizes the significance of enacting gender-sensitive policies, advocating gender quotas, and fostering supportive and inclusive political settings in order to overcome these hurdles and develop gender-inclusive policymaking. The study also emphasizes gender representation's revolutionary power in transforming political discourse and encouraging increased public participation. The findings highlight the critical importance of continuing to advocate for gender equality in politics and addressing the impediments that perpetuate underrepresentation.